Laser Vision Correction on Patients with Sick Optic Nerve: A Case Report - Ming Chen (Case Reports in Ophthalmological Medicine)
This 48-year-old white female with chronic optic disc edema is reported for the discussion of the management for the laser vision correction. Two procedures were considered, one was PRK (photorefractive keratectomy) and the other was LASIK (laser-assisted in-situ keratomileusis). A search strategy was developed to search evidence in the literature to support the decision in the selection of the better procedure for this patient. The evidences also were rigorously appraised for the validity. PRK was selected and performed on the patient with good outcome.